Utilizing a Pediatric Disaster Coalition Model to Increase Pediatric Critical Care Surge Capacity in New York City. (13th June 2017) - Frogel, Michael; Flamm, Avram; Sagy, Mayer; Uraneck, Katharine; Conway, Edward; Ushay, Michael; Greenwald, Bruce M.; Pierre, Louisdon; Shah, Vikas; Gaffoor, Mohamed; Cooper, Arthur; Foltin, George
Abstract: A mass casualty event can result in an overwhelming number of critically injured pediatric victims that exceeds the available capacity of pediatric critical care (PCC) units, both locally and regionally. To address these gaps, the New York City (NYC) Pediatric Disaster Coalition (PDC) was established. The PDC includes experts in emergency preparedness, critical care, surgery, and emergency medicine from 18 of 25 major NYC PCC-capable hospitals. A PCC surge committee created recommendations for making additional PCC beds available with an emphasis on space, staff, stuff (equipment), and systems. The PDC assisted 15 hospitals in creating PCC surge plans by utilizing template plans and site visits. These plans created an additional 153 potential PCC surge beds. Seven hospitals tested their plans through drills. The purpose of this article was to demonstrate the need for planning for disasters involving children and to provide a stepwise, replicable model for establishing a PDC, with one of its primary goals focused on facilitating PCC surge planning. The process we describe for developing a PDC can be replicated to communities of any size, setting, or location. We offer our model as an example for other cities. ( Disaster Med Public Health Preparedness . 2017;11:473–478)